Dette nummers samlede anmeldelser - Payne, Jenny Gunnarsson; Danneskiold-Samsøe, Sofiie; Svensson, Josephine; Spanger, Marlene (Kvinder, Køn & Forskning, 2014)
Marit Melhuus: Problems of Conception: Issues of Law, Biotechnologies and Kinship. Berghahn Books, 2012. Sara Ahmed: On Being Included – Racism and Diversity in Institutional Life. Duke University Press, Durham & London, 2012. Signe Arnfred: Gender Politics in Mozambique: Rethinking Gender in Africa. James Currey, 2011. Hanne Marlene Dahl, Marja Keränen & Anne Kovalainen (red.): Europeanization, Care and Gender: Global Complexities. Palgrave Macmilian, 2011.